PROGRAM APLIKASI OUTLOOK DALAM MEMBENTUK SIKAP POSITIF KARYAWAN KEPADA MEDIA - Maharani Imran; Maharani Imran (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2007)
Outlook Application Program in Order to Increase the Positive Attitude of the Employee to TELKOMRisTI” is a research regarding the activity from one of internal communication media held by TELKOMRisTI employee. The aim of this research is to find out about the outlook application structure, style, and appeal message to increasing the cognitive, affective, and conative aspect of TELKOMRisTI employee using Communication Theory of Persuasion from Hovland, Janis, and Kelly. The research is a kind of a survey research using descriptive method with data collected through: questionnaire, interview, observation, and literature studies. Population in this research are all employee at TELKOMRisTI with 24 employee as a sample which taken based on simple random sampling. The result of this research shows that the Outlook Application massage structure, style are good so that can build the medium cognitive, affective, conative attitude of TELKOMRisTI employee and the other hand shows high cognitive, affective and conative attitude on massage appeal. TELKOMRisTI officer should increase kinds of featur and theme, socialize the e-mail of conduct, and concern about the factualiy and actuality of Aplication Outlook messages.